Genomic Medicine, Precision Medicine, Personalized Medicine: What's in a Name?. Issue 2 (24th May 2013) - Roden, D M; Tyndale, R F
<x xml:space="preserve">Abstract</x> This issue of Clinical Pharmacology & Therapeutics is devoted to genomic medicine, and a reader may reasonably ask what we mean when we use those words. In the initial issue of the journal Genomics in 1987, McKusick and Ruddle pointed out that the descriptor "genome" had been coined in 1920 as a hybrid of "gene" and "chromosome, " and that their new journal would focus on the "newly‐developing discipline of mapping/sequencing (including analysis of the information)." A key milestone in the field was the generation of the first draft of a human genome in 2000, but this success really represents only one of many milestones in the journey from Mendel to MiSeq. Clinical Pharmacology & Therapeutics (2013); 94 2, 169–172. doi:10.1038/clpt.2013.101